Lower Extremity Motor Function Following Complex Adult Spinal Deformity Surgery: Two-Year Follow-up in the Scoli-RISK-1 Prospective, Multicenter, International Study. (18th April 2018) - Lenke, Lawrence G.; Shaffrey, Christopher I.; Carreon, Leah Y.; Cheung, Kenneth M.C.; Dahl, Benny T.; Fehlings, Michael G.; Ames, Christopher P.; Boachie-Adjei, Oheneba; Dekutoski, Mark B.; Kebaish, Khaled M.; Lewis, Stephen J.; Matsuyama, Yukihiro; et al.
Abstract : Background: The reported neurologic complication rate following surgery for complex adult spinal deformity (ASD) is variable due to several factors. Most series have been retrospective with heterogeneous patient populations and use of nonuniform neurologic assessments. The aim of this study was to prospectively document lower extremity motor function by means of the American Spinal Injury Association (ASIA) lower extremity motor score (LEMS) before and through 2 years after surgical correction of complex ASD. Methods: The Scoli-RISK-1 study enrolled 272 patients with ASD, from 15 centers, who had undergone primary or revision surgery for a major Cobb angle of ≥80°, corrective osteotomy for congenital spinal deformity or as a revision procedure for any type of deformity, and/or a complex 3-column osteotomy. Results: One of 272 patients lacked preoperative data and was excluded from the analysis, and 62 (22.9%) of the remaining 271 patients, who were included, lacked a 2-year postoperative assessment. Patients with no preoperative motor impairment (normal LEMS group; n = 203) had a small but significant decline from the mean preoperative LEMS value (50) to that at 2 years postoperatively (49.66 [95% confidence interval = 49.46 to 49.85]; p = 0.002). Patients who did have a motor deficit preoperatively (n = 68; mean LEMS, 43.79) had significant LEMS improvement at 6 months (47.21, p < 0.001) and 2 years (46.12, p = 0.003) postoperatively. The overall percentage of patients (in both groups combined) who had a postoperative LEMS decline, compared with the preoperative value, was 23.0% at discharge, 17.1% at 6 weeks, 9.9% at 6 months, and 10.0% at 2 years. Conclusions: The percentage of patients who had a LEMS decline (compared with the preoperative score) after undergoing complex spinal reconstructive surgery for ASD was 23.0% at discharge, which improved to 10.0% at 2 years postoperatively. These rates are higher than previously reported, which we concluded was due to the prospective, strict nature of the LEMS testing of patients with these challenging deformities. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.